Tacca sanctijosephii (Dioscoreaceae), a new species from Northeast India - Joe, Alfred; Neelamkavil, Sandhya Vincent; Roy, Digpati (Phytotaxa, 2026)
Tacca sanctijosephii, sp. nov. (Dioscoreaceae) is described from moist evergreen forests of Tripura, Northeast India. The species was identified based on detailed morphological study of flowering material obtained from plants cultivated in the Botanical Garden of St. Joseph’s College (Autonomous), Irinjalakuda, Kerala, originally collected from Rajnagar in Kumarghat of Unakoti district, Tripura, India. The new taxon is distinguished from its morphologically allied species Tacca integrifolia by a unique combination of vegetative and floral characters. For ease of comparison, diagnostic vegetative and floral characters of the closely allied species Tacca integrifolia are illustrated.